Dielectric properties of (CuO,CaO2, and BaO)y/CuTl-1223 composites - Mumtaz, M.; Kamran, M.; Nadeem, K.; Jabbar, Abdul; Khan, Nawazish A.; Saleem, Abida; Hussain, S. Tajammul; Kamran, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
We synthesized (CuO, CaO2, and BaO)y/Cu0.5Tl0.5Ba2Ca2Cu3O10–δ (y = 0, 5%, 10%, 15%) composites by solid-state reaction and characterized by x-ray diffraction, scanning electron microscopy, dc-resistivity, and Fourier transform infrared spectroscopy. Frequency and temperature dependent dielectric properties such as real and imaginary part of dielectric constant, dielectric loss, and ac-conductivity of these composites are studied by capacitance and conductance measurement as a function of frequency (10 kHz to 10 MHz) and temperature (78 to 300 K). The x-ray diffraction analysis reveals that the characteristic behavior of Cu0.5Tl0.5Ba2Ca2Cu3O10–δ superconductor phase and its structure is nearly undisturbed by doping of nanoparticles. The scanning electron microscopy images show the improvement in the intergranular links among the superconducting grains with increasing nanoparticles concentration. Microcracks are healed up with the inclusion of these nanoparticles and superconducting volume fraction is also increased. The dielectric properties of these composites strongly depend upon the frequency and temperature. The zero resistivity critical temperature and dielectric properties show opposite trend with the addition of nanoparticles in Cu0.5Tl0.5Ba2Ca2Cu3O10–δ superconductor matrix.